Natural convection heat transfer inside enclosure with various geometries and enhancement methods a review - Abdullah Mohammed, Akeel; Fakhrey Khudheyer, Ahmed (International Journal of Engineering and Technology, 2019)
Natural convection heat transfer from a hot surface to its surrounding enclosure is used in several technological applications especially in microelectronic systems, solar concentrators; thermal storage plants, pressurized water reactors and gas insulated electrical transmission systems. The function of the outer surface of the enclosure is to reduce the heat transfer from the inner hot surface or to protect the inner body in harsh outdoor environment. There are so many researches are conducting on the above same topic in different aspects by changing the position and geometry of the heated surface and the enclosure. In addition to changing the thermal boundary conditions, using of porous media, magnetic field and nano fluid to enhance heat transfer process. In this paper, a review on the influence of a wide range of parameters on the heat transfer process has been investigated. Â Â